Study on properties of fibre ring resonators - Zhou, Benjamin Zhiyao (2017)
In this report, it shows an overview of the characteristics and analysis behind the fibre ring resonator. A simple construction of fibre ring resonator with its beam splitting coupler and optical circulator is shown schematically. It also includes brief descriptions of the various optical components and machines used. The properties of fibre ring resonator will be elaborated specifically in single mode optical fibre application. In this report, it discusses the different properties in both linear and non-linear applications. Both linear and non-linear applications were tested with different coupling ratio optical coupler under continuous wave and pulsed light injection respectively. A set of five couplers with different coupling ratio will be used individually on the fibre ring resonator prototype. From the integrated system of the prototype, the transmission and reflection coefficient obtained in the experimental results match, with little deviations, with the linear aspects of the fibre ring resonator.